IMPLEMENTATION OF EXTRACURRICULAR ACTIVITIES OF DOLANAN DANCE AS A STRENGTHENING IMPLEMENTATION OF CHARACTER EDUCATION - Dyah Purnamastuti Ningrum (Warta Pendidikan | e-Journal, 2021)
The purpose of this study is to describe (1) the effectiveness of the application of extracurricular dance activities to the main value of strengthening the character education of the students (2) the effectiveness of the extracurricular activities of the dance to the role of mutual cooperation gotong royong. Data collection techniques in this study through: Observation, documentation, interviews, questionnaires and tests. The result of this research are: (1) The result of correlation test of character education at the main value in statistic shows 0,762 positive value (2) the result of correlation of student’s parents role with the main value gotong royong at statistic show 0,687 is positive value and show stronger the relationship.